The Organizational Structure and Operational Logic of an Urban Smart Governance Information Platform: Discussion on the Background of Urban Governance Transformation in China. (12th December 2020) - Kang, Junfang; Wang, Xianjun
Abstract : At present, the Chinese government is trying to resolve various social contradictions, such as people's ever-growing need for a better life and unbalanced and inadequate development. To do so, urban governance practices including holistic governance, decentralized and interconnected governance, multiple participatory governance, and smart governance have been developed in China. Urban smart governance supported by mobile Internet, the Internet of Things, quantum computing, big data, artificial intelligence, and other information technologies has also entered the field of vision of academics and administrators. However, the research and practice on the integration of organizational structure and smart governance technology for urban governance in China are still insufficient. Hence, this paper proposes the design of the organizational structure of an urban smart governance platform and presents the "1 +  N " integrated smart information platform and the "power-sharing linkage, one-center and dual-track" platform construction command system. In this system, the functional module of the information platform for smart urban governance is elaborated. This paper contributes to promoting the modernization of China's urban governance capacity, which can enhance social equity and social order, promote social democracy and rule of law, and enhance the efficiency of urban governance.